Eficiência e qualidade de aplicações de fungicidas, por vias terrestre e aérea, no controle de doenças foliares e no rendimento de grãos de soja e milho - Costa, Deise Isabel da (2009)
New equipment and technologies for aerial and ground sprays have been developed, many at the regional level, because weather conditions, inherent in each region, are related to the success or failure of an application of agricultural chemicals. In order to add on a multidisciplinary, some basic knowledge about the control of diseases of plants and technologies for aerial and ground sprays were accomplished in the Tapejara county, state of Rio Grande do Sul, Brazil, (season 2005/06 soybean) and in the Coxilha county, state of Rio Grande do Sul, Brazil, (season 2006/07 maize). In soybean, were evaluated the viability of the chemical control of the powdery mildew (Erysiphe diffusa) and the Asian rust (Phakopsora pachirhizi) through the aerial and ground fungicidal sprays at different day times and ambient conditions. The fungicide Priori-Xtra® (azoxystrobin + ciproconazole) was sprayed at R3 growth stage and 21 days later (R5.3). The experiment conducted in maize crop intended to evaluate the viability of the polysora rust (Puccinia polyssora) and the common helminthosporiose (Exserohilum turcicum) chemical control through various forms of aerial and ground sprays of fungicides. The fungicide Opera® (piraclostrobin + epoxiconazole) was sprayed when the maize showed eight leaves with height between 0.7 m and 0.8 m (feasible height limit for entrance with ground sprayer) and in the tasseling stage and in both moments. Aerial applications performed better than ground sprays. The use of fungicide was feasible and the economic gains depended on the form of application that was adopted. Ground applications, in both crops, cause significant damages by tire tracks, especially in the maize crop